2012
DOI: 10.1080/17441692.2011.626436
|View full text |Cite
|
Sign up to set email alerts
|

Depression among carers of AIDS-orphaned and other-orphaned children in Umlazi Township, South Africa

Abstract: South Africa faces the challenge of supporting the well-being of adults caring for growing numbers of AIDS-orphaned children. These adults play a critical role in responses to the epidemic but little information exists in regards to their mental health needs. This paper reports on findings from n=1599 adults, recruited through representative household sampling, who serve as primary carers for children in Umlazi Township, a HIV endemic community. Overall, 22% of participants were carers of AIDS-orphaned childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…The lack of consistent instruments makes comparisons between groups difficult; however, the markedly higher frequency of depressive symptoms in the INK area may be explained by the unique stressors that the elderly in this area face, such as poverty, crime and the HIV and TB pandemic. [17] Recent crime statistics released by the SA Police Services for 2012/2013 revealed that KwaMashu section E had one of the highest murder rates in the country, with 120 murders recorded for this time period.…”
Section: Article Discussionmentioning
confidence: 99%
“…The lack of consistent instruments makes comparisons between groups difficult; however, the markedly higher frequency of depressive symptoms in the INK area may be explained by the unique stressors that the elderly in this area face, such as poverty, crime and the HIV and TB pandemic. [17] Recent crime statistics released by the SA Police Services for 2012/2013 revealed that KwaMashu section E had one of the highest murder rates in the country, with 120 murders recorded for this time period.…”
Section: Article Discussionmentioning
confidence: 99%
“…These disadvantageous factors, coupled with the fact that most countries in sub-Saharan Africa have no established government social welfare support for families caring for AIDS-affected families, place such families at greater economic and psychological risk in their caregiving role. Caregivers may experience exacerbated chronic health conditions, stress-related somatic complaints, or poor mental health functioning due to the stress to meet their children’s food security, health care, and educational needs (Kuo & Operario, 2009, 2011; Kuo, Operario, & Cluver, 2012). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies indicate that in comparison to caregivers for non-orphaned children, caregivers of AIDS-orphaned children suffer from debilitating mental health outcomes (DeSilva et al, 2008; Kuo & Operario, 2011; Kuo et al, 2012). For example, Kuo et al studied over 1500 adult caregivers in South Africa and found that caregivers of orphaned children were significantly more likely – in comparison to their non-orphan caregivers – to meet the clinical threshold of depression and report elevated levels of anxiety, post-traumatic stress, and overall poor health (Kuo & Operario, 2011; Kuo et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies suggest that becoming a caregiver of a child orphaned by AIDS can elevate risks for poor psychological outcomes, 14,15 possibly due to a number of challenges associated with the increased responsibility of caring for additional children within the household. 16 Other studies indicate individuals living with HIV [17][18][19][20] and adults providing care to individuals living with HIV are at increased risk for poor psychological outcomes.…”
Section: -13mentioning
confidence: 99%
“…Our primary aim was to examine the relationship between differential HIV impacts and caregiver anxiety including: (a) living with HIV but not caring for a child orphaned by AIDS, (b) caring for a child orphaned by AIDS but not living with HIV, (c) and dual HIV effects, defined as caregivers living with HIV while caring for a child orphaned by AIDS, compared to nonaffected caregivers. We chose to focus on anxiety because other psychological studies with this population have examined depression 14,15,31 and stress. 7,37 Our secondary aim was to explore whether stigma mediated the relationship between HIV and anxiety given that stigma may be a salient variable for caregivers experiencing double stigma due to living with HIV and caring for a child orphaned by AIDS.…”
Section: -13mentioning
confidence: 99%